O-181 4D ultrasound guided embryo transfers statistically improve live birth rates - A randomised controlled trial. (6th August 2021) - Nancarrow, L; Tempest, N; Drakeley, A; Hombury, R; Ford, K; Hapangama, D; Russell, R
Abstract: Study question: Does the use of 4D ultrasound to guide embryo transfers improve live birth rates in comparison to the clinical touch technique? Summary answer: 4D ultrasound guided embryo transfers (4DUS) result in significantly higher live birth rates (LBR) in comparison to those performed using the clinical touch technique (CTT)(41%vs28%). What is known already: A previous Cochrane review showed ultrasound guided embryo transfers (ET) improve pregnancy outcomes in comparison to CTT; however there was a large degree of heterogeneity between the studies and the largest study in the review showed no difference between ultrasound guidance and CTT. A further study demonstrated no difference in ongoing pregnancy rates between 2D vs 3D ultrasound guided embryo transfers, however this study did not use LBR as an endpoint and did not report on procedure duration/difficultly, both of which are known to impact ET success rates. Study design, size, duration: This was a prospective, open labelled randomised controlled trial comparing superiority between two techniques for ET (4DUS vs CTT). A total of 320 (n = 160/group) patients were recruited using computer generated randomisation that were centrally distributed in consecutive sealed opaque envelopes between July 2018 to December 2019. Main outcomes were clinical pregnancy rate (CPR) and LBR. Following the procedure, participants completed a survey based on their comfort and satisfaction. Participants/materials, setting, methods: Inclusion criteria included single blastocyst transfer and a normal uterine cavity. Participants were recruited and randomized on the day of ET. Those allocated to the CTT group, had their embryo transferred without ultrasound, depositing the embryo 6cm from the external os. Those in the 4DUS group had their ET using transvaginal 4D ultrasonography and had their embryos deposited at the maximal implantation point (MIP). Main results and the role of chance: Results were available from a total of 295 women (8% attrition rate, CTT n = 153; 4DUS n = 142)). No demographic differences between the two groups (CTT and 4DUS) were noted including age (p = 0.05), BMI (p = 0.29), duration of infertility (p = 0.94), type of infertility (p = 0.68) or embryo quality (p = 0.89). All the 4DUS and 95% of the CTT group were performed by the same practitioner. The 4DUS resulted in significantly higher CPR (50% vs 36% p = 0.015, OR 1.78 (1.12-2.84)) and LBR (41%vs 28%, p = 0.021, OR 1.77 (1.09-2.87)). There were no statistically significant differences between miscarriage (p = 0.494), pregnancy of unknown location (p = 0.141) or ectopic pregnancy rates (p = 0.958) between the two groups. The 4DUS process took significantly longer time compared with the CTT procedure (15.7 vs 10.2 minutes respectively, p < 0.01). The results of the survey showed no statistical difference between patient comfort (p = 0.17) or satisfaction (p = 0.08) between the groups however there were significantly more positive comments in the 4DUS (p < 0.01). In the 4DUS group there was no difference in mean endometrial thickness (P = 0.186) or endometrial volume (p = 0.836) between pregnant and non-pregnant patients. Limitations, reasons for caution: Due to the nature of this trial we were unable to blind the participants due to the obvious differences between the methods. Wallace catheters were used for the CTT and Kitazato catheters for the 4DUS, whilst a methodological weakness; previous meta-analysis has not shown any difference between different soft catheters. Wider implications of the findings: LBRs, when utilizing 4DUS, are significantly higher than the current UK average (41%vs22-23%) and significantly higher than CTT. 4DUS allows for superior imaging of the uterine cavity, tailoring the embryo deposition point specifically to the patient. Further RCTs are required to confirm that 4DUS is the superior technique for ET. Trial registration number: ISRCTN79955797, IRAS 202857